2021
DOI: 10.52547/jfl.9.38.191
|View full text |Cite
|
Sign up to set email alerts
|

Impact of STAD model of Cooperative Learning on Iranian EFL Learners’ Critical Thinking and Motivation

Abstract: This study investigated the impact of cooperative learning on Iranian high schoolEFL learners' critical thinking and motivation. To this end, 142 EFL students were selected based on their performance on the Oxford Quick Placement Test (OQPT), and divided into two heterogeneous experimental groups (EG) receiving treatment through STAD model of cooperative learning, and two control groups (CG) without any treatment. To recognize the entry behaviors of the participants, pretests were run. Then, the same education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 15 publications
2
5
0
1
Order By: Relevance
“…These findings are in line with other studies that previously demonstrated the significant effects of cooperative learning on students’ motivation (Alghamdy, 2019; Bećirović et al, 2022; Gashti, 2021; S. H. J. Liu & Lan, 2016; Lynn Brown, 2021; Moghaddam & Heidari, 2018; Nazari et al, 2021; Neo et al, 2012; Ning & Hornby, 2014; Quinn, 2006). However, some studies have indicated that cooperative learning improves only intrinsic motivation (Lynn Brown, 2021) but not other aspects of motivation (Ning & Hornby, 2014).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These findings are in line with other studies that previously demonstrated the significant effects of cooperative learning on students’ motivation (Alghamdy, 2019; Bećirović et al, 2022; Gashti, 2021; S. H. J. Liu & Lan, 2016; Lynn Brown, 2021; Moghaddam & Heidari, 2018; Nazari et al, 2021; Neo et al, 2012; Ning & Hornby, 2014; Quinn, 2006). However, some studies have indicated that cooperative learning improves only intrinsic motivation (Lynn Brown, 2021) but not other aspects of motivation (Ning & Hornby, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…However, she exposed students to real-life problems that could positively impact their motivation and achievement. Other studies also demonstrated that cooperative learning positively influences learning vocabulary (Gashti, 2021), oral skill (Moghaddam & Heidari, 2018), critical thinking (Nazari et al, 2021), and self-efficacy in the EFL classroom (Saunders-Wyndham & Smith, 2020). Possible explanations for discrepancies in research findings include the fact that people from different cultures cooperate in different ways (Phuong-Mai et al, 2009) and that major complicated relationships exist between culture and the social components of cooperative group activity (Ghahraman & Tamimy, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Salah satu model cooperative learning yang terbukti meningkatkan kemampuan berpikir kritis adalah model Student Team Achievement Divisions (STAD) (Nazari, 2021;Kpiranyam et al, 2021;Supratman, Sirad, & Putri, 2021). Model Student Team Achievement Divisions (STAD) merupakan salah satu model cooperative learning yang paling sederhana sehingga sangat cocok digunakan bagi para guru yang baru menggunakan pendekatan pembelajaran kooperatif selain itu model ini juga sangat mudah untuk diadaptasi karena telah banyak digunakan dalam pembelajaran di bidang matematika, sains, ilmu pengetahuan sosial, bahasa, teknik, dan subjek lainnya (Casey & Fernandez-Rio, 2019).…”
Section: Konsep Model Cooperative Learning Tipe Student Team Achievem...unclassified